2021
DOI: 10.1055/a-1320-4203
|View full text |Cite
|
Sign up to set email alerts
|

Überprüfung eines Schnelltestsystems zur Erfassung der Betahydroxybutyrat-Konzentration im Blut von Milchkühen

Abstract: Zusammenfassung Ziel Das vermehrte Auftreten von Ketose in der Transitphase bei Milchkühen verursacht hohe ökonomische Verluste. Die frühzeitige Identifizierung betroffener Tiere bereits im subklinischen Stadium ermöglicht, die Erkrankungshäufigkeit zu reduzieren und Verluste zu vermeiden. Ziel der Studie war, die Eignung eines mobilen Testgeräts zur Analyse der Betahydroxybutyrat-Konzentration (BHB-Konzentration) in der praktischen Anwendung zu prüfen. Darüber hinaus sollten die mit diesem Gerä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ketosis is a common metabolic disease that occurs in dairy cows during the postpartum transition period that is responsible for considerable long-term economic loss. 24 It is characterized by increased circulating levels of FFA and BHB owing to negative energy. 25 Herein, higher FFA and BHB concentrations and lower blood glucose concentrations in ketotic dairy cows compared with those in healthy cows indicated that the former experience metabolic disorders during early lactation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketosis is a common metabolic disease that occurs in dairy cows during the postpartum transition period that is responsible for considerable long-term economic loss. 24 It is characterized by increased circulating levels of FFA and BHB owing to negative energy. 25 Herein, higher FFA and BHB concentrations and lower blood glucose concentrations in ketotic dairy cows compared with those in healthy cows indicated that the former experience metabolic disorders during early lactation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ketosis is a common metabolic disease that occurs in dairy cows during the postpartum transition period that is responsible for considerable long-term economic loss . It is characterized by increased circulating levels of FFA and BHB owing to negative energy .…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted in accordance with the German Animal Welfare Act and the Saxony Veterinary and Food Safety Office Landesdirektion Sachsen, permit number TVV 33/15. Individual results from the associated overall project have already been published elsewhere (29,(34)(35)(36).…”
Section: Research Permitmentioning
confidence: 99%